Determinants of Halal Tourism Destination Choices Among Young Muslims - Amanda Sadira, Sadira; Anggraini, Ika Khusnia (Islamic Economics and finance in Focus, 2026)
Halal tourism in Indonesia continues to grow, but research examining psychological and digital factors influencing the decision to choose halal tourist destinations among Generation Z and Millennials remains limited. This study aims to analyze the influence of attitude, knowledge, social media, and halal awareness on the decision to choose halal tourist destinations among Muslims aged 18–44 years in Indonesia. The study used an explanatory quantitative approach through an online survey with purposive sampling of 175 respondents. The data were analyzed using multiple linear regression after passing the validity, reliability, and classical assumption tests. The results showed that attitude, knowledge, social media, and halal awareness had a positive and significant effect on the decision to choose a halal tourist destination. The coefficient of determination value of 0.866 indicates that the variation in the decision to choose halal tourist destinations in this model can be explained by the variables tested. These findings show that the halal tourism decisions of the younger generation are influenced by psychological factors, knowledge, and exposure to social media. The implication is that destination managers need to strengthen halal literacy, credible digital content, and Muslim-friendly facilities.